Epidemiological profile of children and adolescents with COVID-19: a scoping review - Fabiane Blanco Silva Bernardino; Lidiane Cristina da Silva Alencastro; Ronaldo Antonio da Silva; Antonia Dinágila do Nascimento Ribeiro; Geovane Roberto de Campos Castilho; Maria Aparecida Munhoz Gaíva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to map the epidemiological profile of children and adolescents with COVID-19 in the world literature. Methods: a scoping review systematized by the Joanna Briggs Institute protocol in the PubMed/MEDLINE, CINAHL, Web of Science, Scopus, Science direct and Google Scholar databases. Articles with children and/or adolescents with laboratory diagnosis of COVID-19 were used. Results: thirty-two articles were included in the review. Most children and adolescents were male, with contamination by family transmission. The most frequent clinical manifestations were fever, cough and diarrhea. Ten studies cited pre-existing condition/disease, and hospital length ranged from one to twenty days. Three deaths were reported and no study presented race/color, education and socioeconomic conditions. Conclusion: it was possible to screen the epidemiological profile with information about age group, sex, probable contamination of the disease, clinical manifestations, presence of pre-existing disease/condition, hospitalization and deaths among children and adolescents with COVID-19.